Case Report: Intravitreal dexamethasone implant as adjuvant treatment for taxane-related cystoid macular edema - Liu, Xujia; Ding, Xiaohua; Lin, Guoqiao (Frontiers in Ophthalmology, 2022)
Taxane-related cystoid macular edema (CME) is a rare bilateral complication of the taxane class chemotherapeutic drug. In this study, we report a 47-year-old man referred to our Eye Center for decreased vision with metamorphopsia. Two weeks prior, he received the last cycle of his six-monthly chemotherapy, including paclitaxel for hypopharyngeal malignancy. The best-corrected visual acuity (BCVA) was 0.4 OD and 0.1 OS. Optical coherence tomography examination showed bilateral CME, and fluorescein angiography (FA) revealed the fluorescein pooling without leakage. Intravitreal 700 μg dexamethasone (DEX) implant was successively applied to the left eye and the right eye. Two months later, the macular morphology recovered to normal. One year after the first visit, the BCVA was 1.0 OD and 0.8 OS with standard macula on OCT. In conclusion, the intravitreal DEX implant is an effective adjuvant treatment for Tanxane-related CME.